Impact analysis of hierarchical honeycomb core sandwich structures. (15th January 2022) - Korupolu, D.K.; Budarapu, P.R.; Vusa, V.R.; Pandit, M.K.; Reddy, J.N.
Abstract: Cellular structures are light weight structures with high specific, impact, flexural strength and stiffness. Hierarchical structures offer higher load-bearing capacity compared to their conventional counter parts. In this study, performance of enhanced hierarchical honeycomb core cellular structures under compression and impact loads is investigated. The hierarchy is proposed by varying the order and the level of the cells. Hierarchical patterns are developed by replacing the vertex cells of regular hexagonal honeycomb with circular cells. The local arrangement of the proposed hierarchical cellular structures is improved to withstand higher loads. The out-of-plane performance of honeycomb structure is enhanced by a hierarchical scheme. As a result, a novel hierarchical second order second level hexagon based hybrid cell has been developed. Furthermore, the influence of sandwiching the cellular structures between face sheets against impact loads is also studied using numerical simulations. In order to transfer the loads efficiently from the top and bottom ends to the mid walls of the unit cell, the structural angle β is introduced as the angle between the normal of the face-sheet and the axis of the unit cell. Such an arrangement is observed to enhance the load distribution in the cellular structures.